2021
DOI: 10.1155/2021/6686644
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Górnicki-Proinov Type Contraction

Abstract: In this paper, we propose a notion of the Górnicki-Proinov type contraction. Then, we prove the uniqueness and existence of the fixed point for such mappings in the framework of the complete metric spaces. Some illustrative examples are also expressed to strengthen the observed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Assume d(z, T z) = ε > 0. It follows from T n x 0 → as n → ∞ that d(T n x 0 , T z) → d(z, T z), which implies that d(T n x 0 , T z) > 0 holds for infinitely many values of n. Then applying (10), we have…”
Section: A Fixed Point Theorem For (ψ − ϕ)-Type Generalized Contractionmentioning
confidence: 97%
See 1 more Smart Citation
“…Assume d(z, T z) = ε > 0. It follows from T n x 0 → as n → ∞ that d(T n x 0 , T z) → d(z, T z), which implies that d(T n x 0 , T z) > 0 holds for infinitely many values of n. Then applying (10), we have…”
Section: A Fixed Point Theorem For (ψ − ϕ)-Type Generalized Contractionmentioning
confidence: 97%
“…Attempting to obtain in preordered set results inspired by the recent work of Karapınar et al [10] encounters serious difficulties and opens the way for further research. Now we present a partial result in this direction.…”
Section: Fixed Point Theorems For Kannan-type Mappingsmentioning
confidence: 99%
“…Among all, the authors observed a very general result in a general setting by using a simulation function. For more interesting results, see, e.g., [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Karapinar-Samet proposed [6] generalized α − ψ-contraction. In this consideration, the role of α admissible mapping is to combine the problem of fixed point of "cyclic contractions" with the same problem in the framework of metric spaces endowed with a"partially ordered set", see, e.g., [7][8][9][10][11][12]. Later, this notion is refined by Popescu [13].…”
Section: Introductionmentioning
confidence: 99%